Infant Attention Is Dynamically Modulated With Changing Arousal Levels. Issue 2 (2nd December 2016) - de Barbaro, Kaya; Clackson, Kaili; Wass, Sam V.
Abstract : Traditional accounts of developing attention and cognition emphasize static individual differences in information encoding; however, work from Aston‐Jones et al. suggests that looking behavior may be dynamically influenced by autonomic arousal. To test this model, a 20‐min testing battery constituting mixed photos and cartoon clips was shown to 53 typical 12‐month‐olds. Look duration was recorded to index attention, and continuous changes in arousal were tracked by measuring heart rate, electrodermal activity, and movement levels. Across three analyses, we found that continuous changes in arousal tracked simultaneous changes in attention measures, as predicted by the Aston‐Jones model. It was also found that changes in arousal tended to precede (occur before) subsequent changes in attention. Implications of these findings are discussed.